Plant bugs (Hemiptera: Miridae) associated with pastures in Colombia - Barreto-Triana, Nancy; Ferreira, Paulo Sergio F.; Osorio-Mejía, Pablo Andrés; Ferreira, Luciano S. Fiuza (Zootaxa, 2018)
Eight species of the family Miridae found in Colombian pastures belong to four genera: Collaria, Cynodonmiris, Neotropicomiris and Stenodema. All species are included in the tribe Stenodemini and are associated with Poaceae grasses. Diagnosis, keys to species and genera, and distribution in Colombian regions as well as the principal host of these species are presented. Habitus and male genital structures illustrations for each species are provided to facilitate their recognition.